A comparison of the carbon footprint of pavement infrastructure and associated materials in Indiana and Oklahoma - Rachel D. Mosier; Sanjeev Adhikari; Saurav K. Mohanty (International Journal of Advances in Applied Sciences, 2020)
Although often overlooked, infrastructure has a significant role in modern society. It is necessary means of transportation for goods and services needed to support commerce. It is this need and the need for continued economic development that causes the continuous infrastructure construction and its’ associated greenhouse gas emissions. Infrastructure construction requires energy to process raw materials, transport, mix and final construction. Greenhouse gas emissions from pavement sections have previously been identified for pavement preservation techniques. This research further evaluates greenhouse gas emissions for typical pavement sections from Indiana and Oklahoma to determine the carbon footprint based on linear foot of pavement. The comparison of CO2e of two typical roadway sections finds the difference in carbon footprint since variation in their minimum roadway. The carbon footprint of typical utility pipe with HDPE produces minimum CO2e and steel produces maximum CO2e. Soil base remediation options produce minimum CO2e and stabilized aggregate base produces maximum CO2e. Carbon offsets are determined by choosing vegetative options, soil remediation methods and appropriate pavement. This study is limited to a few pavement sections with a small variety of typical anticipated carbon offsets that would be seen in roadway construction. The index presented allows users to simply quantify benefits of the carbon offsets.